Jadwal Distribusi dan Citarasa Makanan Berhubungan dengan Sisa Makanan Pasien di Ruang Perawatan Obgyn dan Bedah RSD. dr. Soebandi Jember - Arinda Lironika Suryana; Mailia Yunda Suryadi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background : The hospital food acceptance is still a serious problem. The patient’s acceptance is indicated by the least amount of plate waste. High plate waste causes an intake incompatibility with nutritional needs, which ultimately affects malnutrition. The patient’s plate waste in obstetric and surgical room is still high ≥20%. The distribution timetable and food taste maybe a contributing factor.Objectives : To analyzed the correlation of distribution timetable and food taste with patient’s plate waste at obstetric and surgicall room in dr. Soebandi Hospital, JemberMethods: This study was an analytical survey with a cross sectional design. The sample was 51 subjects, taken by a purposive sampling. Sample were obstetric and surgical patients aged 18-60 years, received regular food and were in a conscious. The distribution timetable was obtained by observing the accuracy of food distribution time span from the kitchen of nutrition instalation untill food arrived at the patient for 3 days. Food taste was obtained through interviews and questionnaires. Plate waste was measured by visual comstock. Data were analyzed by Rank Spearman test.Results : The average plate waste of patients is 27.6%. The plate waste in male and female patient was significantly different (p=0.001). 52.9% subjects with large amounts of plate waste, get hospital food with the right distribution time. The distribution timetable wasn’t significantly correlated with plate waste (p=0.218). Subjects who considered their food taste good, almost all (71.4%) left little food. There was a significant positive correlation between taste of food and plate waste (p=0.001; r=0.471).Conclusions: Food distribution timetable isn’t related to patient’s plate waste. However, food taste is correlated with plate waste. The better of taste food, the less plate waste.ABSTRAK Latar Belakang : Penerimaan makanan rumah sakit masih menjadi masalah serius. Daya terima pasien ditunjukkan dengan banyak sedikitnya makanan tersisa. Tingginya sisa makanan menyebabkan ketidaksesuaian asupan dengan kebutuhan gizi yang akhirnya berdampak malnutrisi. Sisa makanan pasien di ruang obgyn dan bedah masih tinggi ≥20%. Jadwal distribusi dan citarasa makanan kemungkinan menjadi faktor penyebabnya.Tujuan : Menganalisis hubungan jadwal distribusi dan citarasa makanan dengan sisa makanan pasien di ruang perawatan obgyn dan bedah RSD. dr Soebandi Jember.Metode : Jenis penelitian ini survey analitik dengan rancangan cross sectional study. Sampel berjumlah 51 orang, diambil dengan teknik purposive samping. Sampel adalah pasien obsgyn dan bedah berumur 18-60 tahun, mendapat makanan biasa dan kondisi sadar. Jadwal distribusi didapatkan dengan mengamati ketepatan waktu distribusi makanan mulai dari dapur instalazi gizi hingga makanan sampai kepada pasien selama 3 hari. Citarasa makanan diperoleh melalui wawancara dan kuesioner. Pengukuran sisa makanan menggunakan visual comstock. Data dianalisis dengan uji korelasi Rank Spearman.Hasil : Rata-rata sisa makanan pasien di ruang obgyn dan bedah 27,6%. Sisa makanan pada pasien laki-laki dan perempuan berbeda signifikan (p=0,001). Sebanyak 52,9% pasien yang sisa makanannya banyak, mendapatkan makanan dengan jadwal distribusi yang tepat. Jadwal distribusi tidak berhubungan signifikan dengan sisa makanan (p=0,218). Subyek yang menilai citarasa makanannya baik, hampir semuanya (71,4%) menyisakan sedikit makanan. Terdapat korelasi positif yang signifikan antara citarasa makanan dengan sisa makanan (p=0,001; r=0,471).Kesimpulan : Jadwal distribusi makanan tidak berhubungan dengan sisa makanan pasien. Namun, citarasa makanan berhubungan dengan sisa makanan. Semakin baik citarasa makanan semakin sedikit sisa makanan.